Location Analysis in Traditional Markets: Case Study of Ciwastra Traditional Market in Bandung - Arifianti, Ria; Fauzan, Tribowo Rachmat (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Traditional markets play an important role in the economy, especially for the lower middle class. Even though modern minimarkets are increasingly mushrooming, the existence of traditional markets is still needed to meet people's needs. However, choosing the location of the market is very important because it will influence consumer decision making in purchasing goods. Therefore, it is necessary to analyze traditional markets in densely populated areas such as the Ciwastra traditional market located in Bandung City, West Java. This research uses a qualitative methodology with descriptive analysis methods to explain market location analysis, data collection in this research uses interviews, literature studies, and field observations. The results of this research state that the choice of location for Ciwastra Market was quite appropriate with various aspects taken into consideration. It is hoped that relevant policy makers can develop traditional markets so they can compete with modern markets. Ciwasta Market has succeeded in utilizing the purchasing power of the local community, especially lower-middle income households who are the main customers of this market. Its strategic location in a residential area guarantees high accessibility for local consumers. The unique location of Ciwasta Market, close to residential areas and minimarkets, provides a strategic advantage in reaching household consumers.